Influence of impurities and conditions of growing the silicon single crystals by Czochralski method on the value of lifetime of non-equilibrium charge carriers - Воляр, Роман Николаевич (Technology audit and production reserves, 2015)
It is investigated the influence of impurities contained in single-crystal silicon which is grown by the Czochralski method. These impurities are: oxygen, carbon, boron. Also it is investigated an influence of cooling rate of the grown single crystal on the lifetime of non-equilibrium charge carriers. The oxygen concentration was in the range (6,45 ... 9,75)×1017 cm-3, carbon – (1,60 ... 10,20)×1016 cm-3; boron – (1,17 ... 1,70)×1016 cm-3. The cooling rate of the single crystal was varied from 1,8 to 3,6 K/min. It was found that increasing the concentration of boron and oxygen increases the lifetime of the non-equilibrium carriers, and the increase of carbon concentration and the cooling rate of the single crystal silicon lead to reduction of the lifetime of non-equilibrium carriers. To identify factors that have the greatest influence on the lifetime of non-equilibrium charge carriers was developed a mathematical model in the form of the regression equation. Assessment of significance of the regression coefficients of equation was conducted by Student t-test value. Statistical reliability of the resulting multiple regression equation was checked by the total F-test that checks the null hypothesis of statistically insignificant of parameters of developed regression equation and the connection closeness indicator. The developed statistically reliable mathematical model showed that in the investigated ranges of the factors most influence on the lifetime of non-equilibrium charge carriers has a carbon concentration and cooling rate of the silicon single crystal. The concentrations of oxygen and boron in the investigated ranges of factors have less influence on the lifetime of non-equilibrium charge carriers in silicon single crystals.